RESPON BEBERAPA JENIS KOMPOS DAN POC TERHADAP PERTUMBUHAN DAN HASIL KUBIS - Agustina E Marpaung; Bina Br Karo; Susilawati Barus (JURNAL AGROTEKNOSAINS, 2018)
Cabbage are one of the vegetable plants that have extensive planting centers in Karo Regency. Currently almost 100% of farmers still use chemical fertilizers in cabbage cultivation. To keep the soil in good condition, it is very necessary to provide organic fertilizer, both in solid and liquid forms which can keep the chemical, physical and biological properties of the soil good. Therefore a study was conducted which aimed to obtain the right type of compost and liquid organic fertilizer to increase cabbage growth and production. The research was carried out at the Berastagi Experimental farm with andisol soil types, altitude of 1,340 m asl. The activity began in July - September 2018. The study used factorial Randomized Block Design (RBD) with 3 replications. The first factor is the type of compost (K0. Comparator = chicken manure), K1. Cow manure + Chicken manure (1:1) fermentation with EM liquid, K2. Cow manure + Chicken manure (1:1) fermentation with solid bran EM, K3. Cow manure + Chicken manure (1:1) fermentation with solid bran EM and kernel and K4. Cow manure + Chicken manure (1:1) enriched with microorganisms). The second factor is the type of Liquid Organic Fertilizer/LOF (O0. Without LOF, O1. LOF Krinyu + kernel, O2. LOF Krinyu + cow urine + seaweed and O3. LOF Comparator). The results showed that the chicken manure compost was able to increase the growth of cabbage plants. Giving chicken manure compost yields the highest weight and cabbage crop 18.42 cm and 1.53 kg, followed by the Cow manure + Chicken manure (1: 1) enriched with microorganisms accompanied by LOF Krinyu + cow urine + seaweed, ie 18 , 38 cm and 1.30 kg. Giving chicken manure compost produced a significantly higher production, which was 6.99 kg.